Navigating Patriarchy in the Digital Era: The Impact of Gender Stereotypes and Online Campaign Intensity on Female Candidates' Electability in Semarang - Solkah Mufrikhah; Laila Kholid Alfirdaus; Fitriyah .; Nur Hidayat Sardini; Muhammad . (JPW (Jurnal Politik Walisongo), 2026)
This study investigates the dynamics of female electability in Indonesian local politics, situated at the intersection of patriarchal hegemony and technological acceleration. Methodologically, the research employs a quantitative explanatory approach involving 180 respondents. Data were analyzed using multiple linear regression to evaluate the interaction between variables. The results reveal three fundamental findings. First, the Dominance of Digital Strategy in Mitigating Patriarchal Cultural Residues is confirmed, with the model demonstrating solid predictive power (R2 = 0.460$). This affirms that nearly half of the variance in voter support is determined by the effectiveness of digital campaigns. Second, a Shifting of Patriarchal Hegemony through Digital Performative Politics is observed. Statistical analysis highlights a sharp contradiction: while gender stereotypes continue to exert significant negative pressure (β = -0.342$), digital campaigns emerge as a superior positive determinant (β = +0.518$). This disparity signals an "algorithmic disruption," allowing candidates to transcend structural barriers.As a novel contribution, this research formulates The Digital Shield Framework and Strategic Mitigation of Gender Barriers. This framework offers a tactical roadmap for candidates to convert social capital into electoral incentives. The study concludes that the integration of digital intelligence functions as a primary "escalation ladder" to penetrate the glass ceiling, shifting the political landscape toward a meritocracy based on digital performance